RADIOFREQUENCY TURBINATE REDUCTION IMPROVE QUALITY OF LIFE TURBINATE HYPERTROPHY PATIENTS - Arum Kartikadewi; Wahyu Budi Martono; Ratri Cahyaningtyas (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Turbinate Hypertrophy decreases quality of life due to  nasal obstructions symptom. Radiofrequency turbinate reduction  is minimal invasive surgical that expected to maintain nasalfunction.  The surgical procedure compromises the improvement of patients‟  quality of life. There  is nocurrent consensus the difference quality of life before and after the procedure. Cross-sectonal  design was done in 31  turbinate hypertrophy patients  with radiofrequency turbinate reduction.  Before and after the procedure, patient‟s quality of life  was assessed  using a sinonasal outcome test-22 (SNOT-22) questionnaire parameters.  Questionnaire  SNOT-22 scores before and after the procedure was analyzed by t-dependent test. Patients characteristic was 20-39 years old age, employed, has past  allergic  rhinitis. Mean of SNOT-22 total score before procedure  was  60.35 + 7,264 and the mean postoperative total score was 10.19 + 3,103. There were significant differences between  quality of life before and after radiofrequency turbinate reduction ( p <0.0001).  The better improvement symptom are nasal-throat symptom (4-79 %),  head, ear and face symptom (2,6-6,4%), diminish sleep disturbance (58,6-71,6%),disturbance activity reduce 57,4-72,8%,  and physicological stress reduce 2-25,8%. Radiofrequencyturbinate reduction improve  the quality of life turbinate hypertrophy patients  Keywords : Turbinate hypertrophy, Turbinate reduction radiofrequency, SNOT-22